From Kinect video to realistic and animatable MPEG-4 face model: A complete framework - Turban, Laura; Girard, Denis; Kose, Neslihan; Dugelay, Jean-Luc (2015 IEEE International Conference on Multimedia & Expo Workshops (ICMEW), 2015)
The recent success of the Kinect sensor has a significant impact on 3D data based computer applications. This study aims to obtain MPEG-4 compliant realistic and animatable face models from Kinect video. The complete framework for this process includes initially the computation of high quality 3D scans from RGB-D Kinect video, and then the computation of animatable MPEG-4 face models using these high quality scans. This study shows that it is possible to obtain high quality 3D scans and realistic and animatable face models of subjects using lower quality Kinect data.